The activity requirements for spike timing-dependent plasticity in the hippocampus - Buchanan, Katherine; Mellor, Jack (Frontiers in Synaptic Neuroscience, 2010)
Synaptic plasticity has historically been investigated most intensely in the hippocampus and therefore it is somewhat surprising that the majority of studies on spike timing-dependent plasticity (STDP) have focused not in the hippocampus but on synapses in the cortex. One of the major reasons for this bias is the relative ease in obtaining paired electrophysiological recordings from synaptically coupled neurons in cortical slices, in comparison to hippocampal slices. Another less obvious reason has been the difficulty in achieving reliable STDP in the hippocampal slice preparation and confusion surrounding the conditions required. The original descriptions of STDP in the hippocampus was performed on paired recordings from neurons in dissociated or slice cultures utilising single pairs of presynaptic and postsynaptic spikes and were subsequently replicated in acute hippocampal slices. Further work in several laboratories using conditions that more closely replicate the situation in vivo revealed a requirement for multiple postsynaptic spikes that necessarily complicate the absolute timing rules for STDP. Here we review the hippocampal STDP literature focusing on data from acute hippocampal slice preparations and highlighting apparently contradictory results and the variations in experimental conditions that might account for the discrepancies. We conclude by relating the majority of the available experimental data to a model for STDP induction in the hippocampus based on a critical role for postsynaptic Ca2+ dynamics.